ANALISIS KEBUTUHAN PESERTA DIDIK SEBAGAI DASAR PENGEMBANGAN PROGRAM BIMBINGAN KONSELING - Juni Fajar Sari; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The first step in the preparation stage of guidance and counseling program planning is to conduct a needs assessment. Needs assessment is an activity that aims to find the real conditions of students which will be used as the basis for planning guidance and counseling programs. One way to conduct a needs assessment is by distributing AKPD (Angket Kebutuhan Peserta Didik). The purpose of this study is to determine the needs of students in the personal, social, career and learning fields that can be used as a basis for developing guidance and counseling programs in schools so that the programs developed are in accordance with the needs of students. The research subjects used in this study were class X students at one of the State Senior High Schools in Cibinong, Bogor as many as 250 people. Data collection for this study used AKPD (Angket Kebutuhan Peserta Didik) consisting of 50 statement items describing personal, social, career, and learning areas which were entered into Google Form and then filled in by respondents. Based on the results of the study, the personal field was the aspect most chosen by respondents at 45.92% while the career field was the aspect least chosen by respondents at 11.73%. The results of this needs assessment are very helpful for counseling teachers to find out the needs of students to get guidance and counseling services, both counseling services provided individually.